Thermal conductivity of molecular crystals of monoatomic alcohols: from methanol to butanol - Korolyuk, O.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Experimental data on the thermal conductivity κ(T) of some simple alcohols have been compared, analyzedand generalized. The objects of investigation were methyl, protonated and deuterated ethyl, 1-propyl and 1-butyl alcohols in the thermodynamically equilibrium phase with a complete orientational order. The temperature interval was from 2 K to the melting point under the equilibrium vapor pressure. It is found that in the region above the temperature of the maximum thermal conductivity κ(T) deviates from the 1/Т law. This is because the total thermal conductivity has an extra contribution κII(T) of short-lived phonons in addition to κI(T) contributed by propagatingphonons: κ(T) = κI(T) + κII(T). The contribution κI(T) is well described by the Debye–Peierls model allowing for the phonon–phonon processes and scattering of phonons by dislocations. At Т > 40 K the contribution κI(T) obeys the law A/Т and κII(T) is practically temperature-independent. It is shown that the Debye temperature ΘD of alcohol is dependent on the molecular mass as ΘD = 678М –0.42 K and the coefficient А characterizing the intensity of the phonon–phonon scattering increases with the molecular mass of the simple monoatomic alcohol by the law А = 0.85М 0.8 W/m, which suggests a decreasing intensity of the phonon–phonon process.